MECHANISTIC CHARACTERIZATION AND DESIGNING POSSIBLE MOLECULAR LIGAND INTERACTIONS WITH RDRP FROM CHIKV (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
To date, no suitable vaccine or specific antiviral drug is available to treat Chikungunya viral (CHIKV) fever. Hence, it is essential to identify drug candidates that could potentially impede CHIKV infection. The present study focused with the development of Designing Possible Docking and Molecular Ligand Interactions with RdRp from CHIK-V protein based on the crystal structure. When, Rifapentine was interact with RdRp viral protein which were clearly showed the significantly excellent glide score of -5.690530 (Kcal/mol) as well as poor glide score of 2.874727 (Kcal/mol). The docking results showed that among the four ligand molecules Efavirenz have the lowest binding values among the other ligands because it has residue contact with total of 13 residues. Two of them were Glut-31, Glut-46, which are catalytic site residues. It is expected that this ligand could prevented the catalytic process. Rimantadine peptide has hydrogen bond interaction with five other residues and them binded with GLU-28, ASP-38 and ILE-45. Based on docking result visualization, it is known that Rifapentine and Rifampin peptide ligand was bound with RdRp enzyme inside the cavity also viral RNA entry when it covets to begin initiation and elongation process. From this study clearly revealed, the ligands such as Rifapentine, Rifampin and Rimantadine may inhibit the RNA dependent RNA polymerase protein activity in chikungunya virus. Furthermore, the backbone structural scaffolds of these four lead compounds could serve as building blocks when designing drug-like molecules for the treatment of Chikungunya viral fever.